The Reasons For the Permission of Replacement of Wakaf Assets (Istibdal Waqf) in Indonesian Regulations: An Interpretative Study - Musthafa, Musthafa; Bin Hj Abdullah, Luqman; Binti Pauzi, Nurhidayah (al-'adalah, 2022)
Government regulations regarding the implementation of istibdal waqf (replacement of waqf assets) aim to ensure the benefit of waqf assets, so they can last longer and be utilized according to their designation. Unfortunately, an explanation of the reasons for the permissibility of istibdal waqf in Government Regulation 42 of 2006 concerning the Implementation of Law No. 41 of 2004 concerning waqf is not found in the regulation. This obscurity can confuse understanding the reasons for the regulation's permissibility of istibdal waqf. This study aims to explain the reasons for the permissibility of istibdal waqf in the regulation. Thus, from the results of this study, a complete understanding can be obtained dealing with the permissibility of istibdal waqf and preventing the emergence of differences in understanding that can harm waqf assets. This research is classified as library research using a legal interpretation approach. This study found that the reason for the permissibility of istibdal waqf in point an in article 49 (2), Government Regulation of the Republic of Indonesia. No. 42 of 2006 concerning the Implementation of Law Number 41 of 2004 concerning Waqf refers to Government Regulation No. 19 of 2021 concerning the Implementation of Land Procurement for Public Interests. At the same time, the explanation for the permissibility of istibdal waqf in point b relates to waqf assets that cannot be used or utilized following the waqf pledge. Furthermore, the permissibility of istibdal waqf in point c relates to waqf assets that can still be used or utilized.